Ultrasensitive reversible oxygen sensing by using liquid-exfoliated MoS2 nanoparticles. Issue 16 (7th April 2016) - Kim, Yeon Hoo; Kim, Kye Yeop; Choi, You Rim; Shim, Young-Seok; Jeon, Jong-Myeong; Lee, Jong-Heun; Kim, Soo Young; Han, Seungwu; Jang, Ho Won
Abstract : Two-dimensional (2D) molybdenum disulfide (MoS2 ) has been attracting rapidly increasing interest for application in chemoresistive gas sensors owing to its moderate band gap energy and high specific surface area. Abstract : Two-dimensional (2D) molybdenum disulfide (MoS2 ) has been attracting rapidly increasing interest for application in chemoresistive gas sensors owing to its moderate band gap energy and high specific surface area. However, the mechanism of chemoresistive sensing via the adsorption and desorption of gas molecules and the influence of the shape of 2D materials are not well understood yet. Herein we investigate the oxygen sensing behavior of MoS2 microflakes and nanoparticles prepared by mechanical and liquid exfoliation, respectively. Liquid-exfoliated MoS2 nanoparticles with an increased number of edge sites present high and linear responses to a broad range of oxygen concentrations (1–100%). The energetically favorable oxygen adsorption sites, which are responsible for reversible oxygen sensing, are identified by first-principles calculations based on density functional theory. This study serves as a proof-of-concept for the gas sensing mechanism depending on the surface configuration of 2D materials and broadens the potential of 2D MoS2 in gas sensing applications.